Stabilitas Antosianin Serbuk Terung Belanda (Solanum Betaceum Cav.) Terkopigmentasi dan Terenkapsulasi Dengan Perubahan pH - Gayatri Pradnya Andini, Ni Luh Ketut Ayu; Diah Puspawati, Gusti Ayu Kadek; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Tamarillo (Solanum betaceum Cav.) contain bioactive components such as anthocyanin. Anthocyanin in tamarillo act as a source of red pigment. This research aimed to determine the effect of pH on the anthocyanin stability of copigmented and encapsulated tamarillo powder and to determine the right pH to produce the best anthocyanin stability of copigmanted and encapsulated tamarillo powder. This research used a Complete Randomized Design with pH treatment consisted of five levels; pH 3, pH 4, pH 5, pH 6, pH7. Each treatment was repeated three times so obtain 18 experimental units. The data obtained were analyzed using analysis of variance and if the treatment had an significant effect on the test parameters, then continued with the Duncan Multiple Range Test (DMRT). The results showed that pH had a significant effect on anthocyanin color degradation, anthocyanin content, absorbance retention, L* values, a*, b*, hue and chroma. The best best treatment to maintain anthocyanin stability of copigmented and encapsulated tamarillo powder is pH 3 with the anthocyanin color with result degradation of 8.48%, anthocyanin content of 0.63 mg/g, absorbance retention of 96.51%, L* value of 40.03, value of a* 51.07, value of b* 56.30, hue of 47.79° and chroma of 76.01. Tamarillo powder copigmented and encapsulated can be used as a functional food ingredient in food products with an acidic pH.